Institutional conditions of internationalisation of higher education: Mass higher school - D. A. Smaliakou (Russian State Vocational Pedagogical University, 2021)
Introduction. Currently, internationalisation is a priority for the development of higher education, as an institutional component of its academic functioning, both in terms of ensuring the quality of education, and in connection with the implementation of a multi-level integration agenda, in which a modern university is involved. In order to increase the effectiveness of the international dimension of higher education, it remains necessary to clarify a number of theoretical and fundamental questions, among them one of the most important is the problem of the institutional conditions of the academic environment that contribute to the emergence of internationalisation. Mass higher education can be found as fundamental condition and in that relation the clarification of the interrelations between massification and internationalisation of higher education can expand the theoretical understanding of current processes in higher education, providing the necessary theoretical framework for further applied research.The aim of the present article is to investigate the interrelations between the massification and internationalisation of higher education in order to clarify the institutional conditions that contribute to the development of the international dimension of the modern university.Methodology and research methods. The methodological framework of this research involves socio-philosophical tools. In particular, the research is based on a retrospective analysis and philosophical deconstruction of the socio-historical transition of higher education from elite to mass model. Both statistical data and analytical materials on the national conditions of transition to mass higher education are used to investigate the issue.Results. The massification of the higher school became reality due to the historical development of social systems, representing the further evolution of global higher education. Acting as a source of society's emancipation and democratisation, the massification of higher education ensured the reorientation of universities from upbringing needs (ideology) to professional competence (economics). Meanwhile, mass higher education is considered to be the reason of destruction of the imperialist agenda, including the problem of alienated labour. Institutionally, the massification of higher education has become possible due the state-private cooperation. The implementation of this cooperation requires two options: 1) via government subsidies to private higher education, 2) via private investments into public higher education. Mass higher education is an institutional factor of internationalisation development: 1) it creates a need to improve the quality of education; 2) it acts as an instrument of the international integration.Scientific novelty. The connection between mass education and internationalisation of higher education has been found. Mass higher education acts as an institutional factor in the formation of academic demand for the development of internationalisation processes: 1) forming the need to improve the quality of education; 2) acting as one of the tools for implementing the integration agenda. The absence of processes of massification and internationalisation in the modern system of higher education may indicate on fundamental barriers in the national development of a particular state.Practical significance. The results obtained will contribute to further fundamental research in the fields of philosophy and sociology of education. Moreover, the present findings could be applied as a theoretical basis for further practical research on modern processes of higher education development.